Statistical and Reliability Analysis of the Iran Railway System as a Complex Network - Melika Mosayyebi; Hadi Shakibian; Reza Azmi (International Journal of Web Research)
The transportation networks analysis aims to investigate the system's structural characteristics and dynamical evolution to evaluate the transit services. In this regard, the topological characteristics of the Iran railway network have been studied and compared to two well-studied railway networks, China and Spain. Also, the network vulnerability to station failures has been studied based on different attacks. Accordingly, in the first step of this work, the city stations have been extracted from Iran railway information to construct the network. Then, some structural properties, including the degree distribution, betweenness centrality, clustering coefficient, and distance distribution, have been analyzed for three networks. Finally, the network reliability has been evaluated using a random as well as adversarial attack. The structural analysis reveals that the Iran railway network would require some structural optimization to improve the economic benefits. Based on the vulnerability investigation, the network efficiency of the network will be dropped more quickly utilizing the maximum betweenness attack. In addition, as it were, little parts of the network seem to keep their usefulness as the estimate of the giant component is diminished exceptionally strongly when less than 20% of nodes are expelled from the network haphazardly or intentioned.